PEMAKNAAN BRAND CHINA (Studi Fenomenologi Pada Millennial Pengguna Mobil Wuling di Surabaya) - Yuniar, Alda Mega (The Commercium, 2022)
This study examines how the meaning of informants regarding a brand originating from aparticular country. The purpose of this study was to find out and describe the behavior orphenomena that exist in society, especially Surabaya residents about the millennial'sperception or view of a new automotive brand from China named Wuling in Indonesia. Thebackground of this research is the rise of Wuling car users in the city of Surabaya,considering stereotype of China's image on negative aspect of product quality. Therefore, theresearcher wants to know the background of users who consume Wuling brand and how theyperceive Wuling brand and the current state of China. This study uses a qualitative methodwith a phenomenological approach. Data collection techniques with interviews, participantobservation, and literature study. The results obtained from interview process of informantsindicate that negative stereotypes about China, which is famous for its counterfeit productswith low prices and quality, have begun to erode over time and China's efforts to improve it,one of which is by presenting Wuling products so that consumers have perspectives andmeanings. positive towards Wuling and China.Keywords: Brand Image, Country of Origin, Consumer Behavior